ANALISIS NERACA AIR PADA JARINGAN IRIGASI DESA KEDAWUNG KECAMATAN MOJO KABUPATEN KEDIRI DALAM PEMENUHAN AIR IRIGASI - Santoso, Rani Rachmad; Saves, Faradlillah (LPPM Universitas Bina Bangsa, 2023)
This research aims to analyze the water balance in the irrigation network in Kedawung Village, Mojo District, Kediri Regency, with a focus on irrigation water supply. Irrigation water is an important factor in agriculture, and the success of an irrigation system is highly dependent on the availability of sufficient and efficient water. The research method involves field surveys to collect data regarding water sources, water distribution, and irrigation water use. In addition, weather and rainfall data were also taken to assess the influence of climate factors on irrigation water availability. The water balance data analyzed includes the volume of water entering the irrigation network, the volume of water used for agriculture, and the volume of water lost due to evaporation and soil infiltration. The results of the water balance analysis will be used to evaluate the efficiency of irrigation water use in Kedawung Village. In addition, this research will also evaluate the adequacy of irrigation water to support local agriculture. If there is a shortage of irrigation water, this research can provide recommendations for improving the irrigation system or water source management.Thus, it is hoped that this research can provide valuable information for local governments, farmers and other stakeholders in an effort to increase agricultural productivity and meet irrigation water needs in Kedawung Village